2021
DOI: 10.1038/s41467-021-27038-5
|View full text |Cite
|
Sign up to set email alerts
|

Defactinib inhibits PYK2 phosphorylation of IRF5 and reduces intestinal inflammation

Abstract: Interferon regulating factor 5 (IRF5) is a multifunctional regulator of immune responses, and has a key pathogenic function in gut inflammation, but how IRF5 is modulated is still unclear. Having performed a kinase inhibitor library screening in macrophages, here we identify protein-tyrosine kinase 2-beta (PTK2B/PYK2) as a putative IRF5 kinase. PYK2-deficient macrophages display impaired endogenous IRF5 activation, leading to reduction of inflammatory gene expression. Meanwhile, a PYK2 inhibitor, defactinib, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 67 publications
0
16
0
Order By: Relevance
“…IRF5 can be phosphorylated by several kinases including TAK1, IKKβ, and Pyk2 73 . In the absence of CXCL4 costimulation, TLR8-induced activation of IRF5 is mediated by TAK1 and IKKβ, with a minor role for TBK1 14 , 64 ; these kinases can phosphorylate IRF5 and/or its upstream adapter TASL.…”
Section: Discussionmentioning
confidence: 99%
“…IRF5 can be phosphorylated by several kinases including TAK1, IKKβ, and Pyk2 73 . In the absence of CXCL4 costimulation, TLR8-induced activation of IRF5 is mediated by TAK1 and IKKβ, with a minor role for TBK1 14 , 64 ; these kinases can phosphorylate IRF5 and/or its upstream adapter TASL.…”
Section: Discussionmentioning
confidence: 99%
“…[ 16 , 19 , 47 , 58 ] Other studies demonstrated its effects on secretion of proinflammatory cytokines from macrophages, such as IL‐1 β and IL‐18 [ 59 ] or IL‐6, TNF ‐α , and IL‐12. [ 60 ] Interestingly, PYK2 was found to regulate inflammatory response in the gut via direct binding and phosphorylation of IRF5 (Interferon regulating factor 5). [ 60 ] Here we show that PYK2 ablation inhibits CCL2 secretion by BC cells (Figure 3D,E ) and CCR2 expression in macrophages (Figure 6E, G, I ), thereby impairing CCL2–CCR2 signaling and consequently TAM recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…[ 60 ] Interestingly, PYK2 was found to regulate inflammatory response in the gut via direct binding and phosphorylation of IRF5 (Interferon regulating factor 5). [ 60 ] Here we show that PYK2 ablation inhibits CCL2 secretion by BC cells (Figure 3D,E ) and CCR2 expression in macrophages (Figure 6E, G, I ), thereby impairing CCL2–CCR2 signaling and consequently TAM recruitment. Indeed, previous reports demonstrated the inhibitory effects of CCL2 neutralizing antibodies on breast cancer growth, metastasis, and TAM recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…IRF5 can be phosphorylated by several kinases including TAK1, IKKβ and Pyk2 72 . In the absence of CXCL4 costimulation, TLR8-induced activation of IRF5 is mediated by TAK1 and IKKβ, with a minor role for TBK1 14, 63 ; these kinases can phosphorylate IRF5 and/or its upstream adaptor TASL.…”
Section: Discussionmentioning
confidence: 99%